ANALYSIS OF BANK INDONESIA RATE OF RETURN ON ASSETS AT THE PT. BANK MANDIRI TBK MANADO - Lalujan, Deisy Natalia; Pelleng, Frendy A.O.; Tumbel, Tinneke (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
ABSTRACT: This study aimed "to determine the influence of the BI Rate to Return On Assets (ROA) at Bank Mandiri (Persero) Tbk". This research uses descriptive method with quantitative approach. The data used in this research is secondary data by source and by the dimension of time using time series data (time series). In this study, the time series of data used is the data on a monthly basis in the period January 2013 s / d December 2015. The data collected were then analyzed by applying descriptive statistical analysis techniques and simple regression analysis and correlation of product moment.The results of the study were presented as follows: (1) that in the study period, the variable BI rate positive and significant impact on Return On Asset (ROA). (2) that the increase in ROA of 12.4% co-determined or influenced by the BI rate, while the remaining 87.6% is influenced by other factors not examined in this study.Thus, it can be concluded that the hypothesis which states "It is believed that the BI Rate effect on Return On Assets (ROA) PT. Bank Mandiri (Persero) Tbk "validity can be tested empirically, as well as justify terori-the underlying theory.To optimize the reception ROA at PT. Bank Mandiri (Persero) Tbk, required government policies, especially Bank Indonesia to control the value of BI-Rate effective and competitive so as to stimulate the real sector thus encouraging the proper functioning of banks as financial services, which in turn will increase the ROA of the bank itself.Keywords: BI-Rate, Return on Assets, Bank Mandiri.